2011
DOI: 10.1007/s12646-011-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Whose Decision is it? Organ Donation Attitudes Among Young UK South Asians

Abstract: A questionnaire study examined organ donor card holding rates and attitudes to organ donation among young adult British South Asians and Whites attending institutions of higher education in the UK. There were 382 respondents (166 male, 216 female, average age 21.8 years): 107 Indian (Hindu or Sikh), 104 Pakistani/Bangladeshi (Muslim) and 171 White (Christian or of no religion). Overall, 33% of White but only 9% of South Asian respondents had a donor card. Among Whites, only 6% thought their parents would find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…It means that relatives may either authorise the retrieval of organs despite the deceased's explicit refusal, or oppose the retrieval of organs against the deceased's explicit consent (also called "family veto"). Thirteen studies addressed this question (24,25,27,29,42,43,45,49,50,(52)(53)(54)(55). Five addressed it in general terms, eight addressed the specific question of the family's capacity to veto the deceased's consent, and none addressed the specific question of the family's capacity to authorise organ retrieval despite the deceased's refusal.…”
Section: Should the Family Be Able To Overrule The Deceased's Wishes (Full Authority)?mentioning
confidence: 99%
“…It means that relatives may either authorise the retrieval of organs despite the deceased's explicit refusal, or oppose the retrieval of organs against the deceased's explicit consent (also called "family veto"). Thirteen studies addressed this question (24,25,27,29,42,43,45,49,50,(52)(53)(54)(55). Five addressed it in general terms, eight addressed the specific question of the family's capacity to veto the deceased's consent, and none addressed the specific question of the family's capacity to authorise organ retrieval despite the deceased's refusal.…”
Section: Should the Family Be Able To Overrule The Deceased's Wishes (Full Authority)?mentioning
confidence: 99%
“…We are currently investigating the latter issue using other datasets. It might also be the case that some groups were exaggerating their charitable donations, as has been found in organ donations (Joshi, 2011). Again we do not have administrative records from charities to check.…”
Section: Resultsmentioning
confidence: 98%
“…The somewhat divided opinions of scholars appear to be reflected in the considerable confusion which exists within the Muslim community about organ donation. Studies have shown that many Muslims think living and deceased organ donation are not allowed in Islam, which can negatively influence their attitudes toward organ donation and transplantation . Other studies found that lack of public knowledge and understanding of the Islamic rulings on organ donation and transplantation is the major culprit .…”
Section: Resultsmentioning
confidence: 99%
“…It is a difficult subject to breach due to religious sensitivities, and many believe that it is not important enough . Compared to non‐Muslim Caucasians and Indians, Muslims from Pakistan and Bangladesh were more likely to indicate that their parents would find it upsetting to discuss their accidental death or even the issue of signing a donor card . How family relations may be affected as a result of living donation or lack thereof was an important consideration for participants in a Pakistani study, many of whom believe that donation could lead to potential conflicts between relatives …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation